2015
DOI: 10.3758/s13423-015-0954-9
|View full text |Cite
|
Sign up to set email alerts
|

What a car does to your perception: Distance evaluations differ from within and outside of a car

Abstract: Almost a century ago it was first suggested that cars can be interpreted as tools, but consequences of this assumption were never tested. Research on hand-held tools that are used to manipulate objects in the environment suggests that perception of near space is extended by using tools. Literature on environment perception finds perception of far space to be modulated by the observer's potential to act in the environment. Here we argue that a car increases the action potential and modulates perception of far s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 62 publications
(60 reference statements)
1
12
0
2
Order By: Relevance
“…Mainly, modern authors are studying the features of the scheme of human body. Recent studies have shown that the body schema has high plasticity and is able to integrate external objects into its structure that are in physical contact with the individual—for example, the tools used by it [22,23,24,25,26,27,28,29]. These facts are consistent with the idea of considering a tool as a probe [21].…”
Section: Introductionsupporting
confidence: 60%
“…Mainly, modern authors are studying the features of the scheme of human body. Recent studies have shown that the body schema has high plasticity and is able to integrate external objects into its structure that are in physical contact with the individual—for example, the tools used by it [22,23,24,25,26,27,28,29]. These facts are consistent with the idea of considering a tool as a probe [21].…”
Section: Introductionsupporting
confidence: 60%
“…This results in an expansion of peripersonal space and an acute awareness of the area around the cane's tip (Serino et al, 2007). Similar effects are observed in numerous tools spanning the complexities of a rake through an automobile (Iriki et al, 1996;Sposito et al, 2012;Moeller et al, 2016). However, at no point do these users perceive their tools as a part of their bodies as they do not engage all the key mechanisms of embodiment.…”
Section: Self-location and Tool-incorporationmentioning
confidence: 88%
“…Of further relevance to human-machine cooperations, there appears to be a link between tool-use proficiency and the changes in peripersonal space that accompany tool-incorporation (Sposito et al, 2012;Biggio et al, 2017). For instance, experienced drivers underestimate distances in front of their vehicles (Moeller et al, 2016), and skilled archers perceive their targets as larger (Lee et al, 2012). Therefore, further exploring toolincorporation and how cooperative machines may engage the requisite sensorimotor mechanisms may be an important avenue to accelerating user proficiency.…”
Section: Self-location and Tool-incorporationmentioning
confidence: 99%
“…For example, archers judge a particular target as being larger when they use bow stabilizers, which makes them feel better about their coordination and control abilities (Lee et al, 2012). Similarly, drivers underestimate egocentric distances to a larger extent compared to pedestrians (Moeller, Zoppke, & Frings, 2016), as being in a car boosts their potential of reaching distant targets without investing important physical resources. Moreover, since drivers tend to identify themselves with the car they are driving, they extend the perception of their body in space and time (also see Berti & Frassinetti, 2000), which makes distances appear shorter.…”
Section: Introductionmentioning
confidence: 99%